THE INFLUENCE OF PRICE, WORD OF MOUTH, AND SERVICE QUALITY ON FAST FOOD PURCHASING DECISIONS SABANA FRIED CHICKEN, CILINCING BRANCH, NORTH JAKARTA - Irfan Arif Husen; Desy Amaliati Setiawan (Bajang Institute, 2023)
Abstract This study aims to determine the influence of price, word of mouth, and service quality on purchasing decisions of fast food consumers at Sabana Fried Chicken Cilincing Branch, North Jakarta. The research approach is quantitative with causal associative research methods. The population in this study were consumers of Sabana Fried Chicken, Cilincing Branch, North Jakarta, while the research sample was 100 consumers of Sabana Fried Chicken, Cilincing Branch, North Jakarta who met the criteria. The data in this study are primary data by distributing questionnaires. The data analysis technique used is path analysis using SmartPLS 3.0. The results of the study concluded that 1) Price had a positive and significant influence on purchasing decisions for fast food consumers at Sabana Fried Chicken Cilincing Branch, North Jakarta, 2) Word of mouth had a positive and significant influence on purchasing decisions for fast food consumers in Sabana. Fried Chicken Cilincing North Jakarta Branch, 3) Service quality has a positive and significant influence on purchasing decisions for fast food consumers at Sabana Fried Chicken Cilincing North Jakarta Branch.